GAMBARAN PENGETAHUAN, SIKAP, DAN PERILAKU PERLINDUNGAN TERHADAP PAPARAN SINAR ULTRAVIOLET PADA WISATAWAN MANCANEGARA DI PANTAI KUTA - Anggraheni, Sukma; Manangkot, Meril Valentine; Utami, Kadek Cahya (Coping: Community of Publishing in Nursing, 2024)
Ultraviolet exposure obtained during tourism activities can causes adverse effects on the health of tourists. These adverse effects include disorders of the eyes and skin to a decrease in the immune system. Protection against ultraviolet exposure is the main prevention strategy that can be done by tourists against various bodily damage due to high ultraviolet radiation. Knowledge is one of the factors that influence attitudes and behavior. If attitudes and behavior are not based on sufficient knowledge, it will produce inadequate attitudes and protective behaviors. This research is a quantitative research with observational descriptive method. The samples in this study were 81 foreign tourist selected using consecutive sampling techniques. Data collection was carried out for 14 days in May 2020 by distributing questionnaires through google form and analyzing data using univariate analysis. The results of this study indicate that the knowledge of foreign tourist is included in the good category (63%), the attitude is quite good (42%), and the behavior is not good (54,3%). The researcher recommends Puskesmas and Tourism Clinics to carry out prevention programs or efforts to promote tourism health programs related to protection measures and health risks due to ultraviolet light exposure, and the nursing profession can develop their professional role in tourism nursing to promote adequate protective behaviors for tourists.